Filtering failure: the impact of automated indexing in Medline on retrieval of human studies for knowledge synthesis - Nicole Askin; Tyler Ostapyk; Carla Epp (Journal of the Medical Library Association)
Objective: Use of the search filter ‘exp animals/ not humans.sh’ is a well-established method in evidence synthesis to exclude non-human studies. However, the shift to automated indexing of Medline records has raised concerns about the use of subject-heading-based search techniques. We sought to determine how often this string inappropriately excludes human studies among automated as compared to manually indexed records in Ovid Medline.